Analysis of the configuration of the acoustic field of loudspeaker systems excited with a sinusoidal signal - HOJAN, Edward (Archives of Acoustics, 1980)
The paper discusses the accuracy of the approximation of the acoustic pressure distribution radiated by loudspeaker systems with the pressure distribution radiated by a flat circular membrane. The far and near field ranges of loudspeaker systems were determined and the effect of the irregularity of the acoustic pressure distribution in the near field of the systems on their amplitude and frequency characteristics was investigated.